Atypical capillary malformations with subsequent diplegia: A difficult case of capillary malformation‐arteriovenous malformation syndrome. Issue 1 (20th November 2019) - Plumptre, Isabella; Robertson, Fergus; Rennie, Adam; James, Greg; Syed, Samira B.
Abstract: Capillary malformation‐arteriovenous malformation syndrome (CM‐AVM) is a rare condition associated with mutations in the genes RASA1 and EPHB4 . We present a challenging case of CM‐AVM in a 17‐month‐old boy with permanent diplegia from an undiagnosed arteriovenous malformation underlying a large atypical capillary malformation over the lower thoracic spine. This case demonstrates that clinicians should have a low threshold for neuroimaging in the context of new neurologic symptoms in patients with atypical capillary malformations.